Plant-herbivore interactions along ecological gradients in tropical rainforest: Drivers of network structure and specialisation - Redmond, Conor (Jihočeská univerzita, 2019)
This thesis concerns the community ecology of Lepidopteran herbivores and their host plants in rainforests of Papua New Guinea. We specifically focus on examining the drivers of plant-herbivore interaction network structure and herbivore specialisation across rainforest succession and elevation. Using one of the most comprehensive and unique datasets of its kind, gathered using a 'whole forest' approach, we investigate how networks are structured in young secondary, mature secondary and primary forest. Furthermore, we revisit a classic ecological question, exploring specialisation of herbivores and how abiotic and biotic factors might influence this. We show that an understanding of host community properties including phylogeny, physical structure and theorised defensive investment can be used to explain interaction network structure. We also find that specialisation changes with elevation, guild type and habitat use in ways which are difficult to predict. We finish by analysing and presenting our relatively novel methodological approach. It is our hope that it can gain wider adoption thus facilitating broader comparative studies.
Plant-herbivore interactions along ecological gradients in tropical rainforest: Drivers of network structure and specialisation